Fukuoka criteria accurately predict risk for adverse outcomes during follow-up of pancreatic cysts presumed to be intraductal papillary mucinous neoplasms. Issue 10 (7th July 2016) - Mukewar, Saurabh; de Pretis, Nicolo; Aryal-Khanal, Anupama; Ahmed, Nazir; Sah, Raghuwansh; Enders, Felicity; Larson, Joseph J; Levy, Michael J; Takahashi, Naoki; Topazian, Mark; Pearson, Randall; Vege, Santhi S; et al.
Abstract : Objective: Fukuoka consensus guidelines classify pancreatic cystic lesions (PCLs) presumed to be intraductal papillary mucinous neoplasms (IPMNs) into Fukuoka positive (FP) (subgroups of high-risk (HR) and worrisome features (WFs)) and Fukuoka negative (FN) (non-HR feature/WF cysts). We retrospectively estimated 5-year risk of pancreatic cancer (PC) in FN, WF and HR cysts of patients with PCL-IPMN. Design: From Mayo Clinic databases, we randomly selected 2000 patients reported to have a PCL; we excluded inflammatory or suspected non-IPMN cysts and those without imaging follow-up. We re-reviewed cross-sectional imaging and abstracted clinical and follow-up data on PCL-IPMNs. The study contained 802 patients with FN cysts and 358 with FP cysts. Results: Patients with PCL-IPMN had median (IQR) follow-up of 4.2 (1.8–7.1) years. Among FN cysts, 5-year PC risk was low (2–3%) regardless of cyst size (p=0.67). After excluding events in the first 6 months, 5-year PC risk remained low (0–2%) regardless of cyst size (p=0.61). Among FP cysts, HR cysts (n=66) had greater 5-year PC risk than WF cysts (n=292) (49.7% vs 4.1%; p<0.001). In HR cysts, 3-year PC risk was greatest for obstructive jaundice versus enhancing solid component or main pancreatic duct >10 mm (79.8% vs 37.3% vs 39.4%, respectively; p=0.01). Conclusions: Fukuoka guidelines accurately stratify PCL-IPMNs for PC risk, with FN cysts having lowest and HR cysts having greatest risk. After 6-month follow-up, WF and FN cysts had a low 5-year PC risk. Surveillance strategies should be tailored appropriately.